2020
DOI: 10.3390/ijerph17072327
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Policy Instruments on Integrated Care in China: Based on Documents Content Analysis

Abstract: Facing the aggravating trend of an aging population and a fragmented medical service delivery system, the Chinese Central Government has introduced a series of policies to promote the development of integrated care against the background of the “Healthy China Strategy”. The achievement of integrated care depends on the choice of policy instruments. However, few studies have focused on how policy instruments promote the practice of integrated care in China. This article aims to obtain a deeper understanding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…However, in the field of elderly care services, most scholars categorize policy instruments into environmental, supply-based, and demand-based policies ( 22 ). Yue divided the integrated care policy for older people into supply-side, demand-side, and environmental policy instruments, and found that environmental policy instruments are the most frequently used, supply-side policies are preferred, while demand-side policy instruments are relatively inadequate ( 23 ). Xiu found that China's local care policies for older people can be classified into supply, demand, and environmental policy instruments ( 24 ).…”
Section: Literature and Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the field of elderly care services, most scholars categorize policy instruments into environmental, supply-based, and demand-based policies ( 22 ). Yue divided the integrated care policy for older people into supply-side, demand-side, and environmental policy instruments, and found that environmental policy instruments are the most frequently used, supply-side policies are preferred, while demand-side policy instruments are relatively inadequate ( 23 ). Xiu found that China's local care policies for older people can be classified into supply, demand, and environmental policy instruments ( 24 ).…”
Section: Literature and Theorymentioning
confidence: 99%
“…We here took a very commonly used measure to calculate policy quantification ( 12 , 22 , 23 ). Based on the calculation of TS , the comprehensiveness, consistency, and balance of different policy instrument mixes within the same dimension and different policy indicator mixes within the same policy were measured.…”
Section: Policy Instrument MIXmentioning
confidence: 99%
“…In response to the above problems, the government began to launch a new round of health reform in 2009,13–15 aiming at optimising the distribution of health resources, strengthening the capacity of primary care and guiding residents to seek medical treatment from PHIs 16 17. Reconstructing the PHC system is the focus of this reform,13 15 and it is also the key to realising the reform goal.…”
Section: Introductionmentioning
confidence: 99%
“…In China, CMNC is regarded as an integration of care and medical resources for older adults. It is a new care model that integrates medical care, rehabilitation, life care, elderly care, and other services to provide smooth and coherent services for older adults (Yue et al, 2020 ). Similar services are usually called “long-term care” (LTC) or “integrated care” in other countries.…”
Section: Introductionmentioning
confidence: 99%